Roads taken : the great Jewish migrations to the new world and the peddlers who forged the way - Diner, Hasia R. (Yale University Press, 2015)
Between the late 1700s and the 1920s nearly one third of the world's Jews emigrated to new lands, often the paths paved by intrepid peddlers who preceded them. Hasia Diner tells the story of these remarkable people who sought opportunities away from home.